2020
DOI: 10.1038/s41556-020-0473-4
|View full text |Cite
|
Sign up to set email alerts
|

Hrd1 forms the retrotranslocation pore regulated by auto-ubiquitination and binding of misfolded proteins

Abstract: During endoplasmic-reticulum-associated protein degradation (ERAD), misfolded proteins are polyubiquitinated, extracted from the ER membrane and degraded by the proteasome 1-4. In a process called retrotranslocation, misfolded luminal proteins first need to traverse the ER membrane before ubiquitination can occur in the cytosol. It was suggested that the membrane-embedded ubiquitin ligase Hrd1 forms a retrotranslocation pore regulated by cycles of autoand deubiquitination 5-8. However, the mechanism by which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 52 publications
5
70
0
Order By: Relevance
“…Our findings reveal Hrd1-mediated translocation of membrane substrates is dispensable of its partner component, Hrd3, as well as its ubiquitination activity. Recent studies suggest Hrd1-mediated translocation of ERAD-L occurs through self-ubiquitination activity of Hrd1, which has also been shown to be regulated by Hrd3 ( Baldridge and Rapoport, 2016 ; Peterson et al., 2019 ; Vasic et al., 2020 ). This led us to posit whether HRD complex remodeling in the suppression pathway negatively affects ERAD-L. CHX-chase assay was used to monitor the degradation rate of ERAD-L substrates, CPY∗ and KHN, in dfm1Δ suppressed cells overexpressing SUS-GFP as well ( Figures S3 A and S3B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings reveal Hrd1-mediated translocation of membrane substrates is dispensable of its partner component, Hrd3, as well as its ubiquitination activity. Recent studies suggest Hrd1-mediated translocation of ERAD-L occurs through self-ubiquitination activity of Hrd1, which has also been shown to be regulated by Hrd3 ( Baldridge and Rapoport, 2016 ; Peterson et al., 2019 ; Vasic et al., 2020 ). This led us to posit whether HRD complex remodeling in the suppression pathway negatively affects ERAD-L. CHX-chase assay was used to monitor the degradation rate of ERAD-L substrates, CPY∗ and KHN, in dfm1Δ suppressed cells overexpressing SUS-GFP as well ( Figures S3 A and S3B).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in our first studies of Dfm1, its dedicated route of ERAD-M even applies to Hrd1 itself: in conditions where Hrd1 self-ubiquitination leads to its very rapid degradation, Dfm1 is absolutely required for Hrd1 retrotranslocation, despite Hrd1's clearly demonstrated role as a ERAD-L retrotranslocon ( Neal et al., 2018 ). This strict boundary makes sense, considering that Hrd1 undergoes an elaborate cycle of self-ubiquitination and de-ubiquitination in the course of its dual roles as a ligase and a lumenal retrotranslocon ( Peterson et al., 2019 ; Vasic et al., 2020 ). If Hrd1 could mediate its own retrotranslocation in normal circumstances, that might lead to catastrophic loss of this key quality control factor in the course of its normal molecular duty cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, this study and others suggest that a growing number of proteins possess the ability to retrotranslocate quality-control substrates out of or through lipid bilayers. These include, but as we show are not limited to, Hrd1, Dfm1, Doa10, and the Asi complex ( Baldridge and Rapoport, 2016 ; Schoebel et al ., 2017 ; Neal et al , 2018 , 2020; Natarajan et al , 2020 ; Schmidt et al , 2020 ; Vasic et al , 2020 ; Wu et al , 2020 ). While redundancy is a common feature of protein-quality-control pathways, it will be interesting to further dissect the biochemical and cell-biological nuances that necessitate these dedicated channels.…”
Section: Discussionmentioning
confidence: 99%
“…HRD1, Derlin-1, and Sec61 have been considered potential components of the retrotranslocon [ 20 , 21 , 22 , 23 ]. Recent studies based on cryogenic electron microscopy [ 24 , 25 ] and electrophysiological analysis [ 26 ] revealed that yeast HRD1 forms a retrotranslocation pore. In mammals, the Derlin family consists of three members: Derlin-1, Derlin-2, and Derlin-3.…”
Section: Introductionmentioning
confidence: 99%